A expansão do crédito e a trajetória de endividamento e inadimpleência no Brasil no período pós-real - Rocha, Vitor Leitão (2013)
Starting at the various proxies in series for credit loans, poor payment history and borrowing debts provided by the Central Bank of Brazil and Serasa Experian, this study sought to evaluate how the monetary authority in Brazil deals with the credit offer after economic stability. The investigation was further broken down into six levels, namely: households, firms of public and private sectors, the automotive industry and housing between July 1994 and April 2012 and the prerequisite for a policy of a liable lending option is that it does not generate elevated and disordered indicators of debts and delinquency. The results of the estimates found here suggest that the long-term evolution of the credit indicators is accompanied by the indebtedness and delinquency, a fact which implies the need to adopt measures to control the increase of indebtedness and reduce delinquency in the country; aiming at the stability of the national financial system.